d=4 as the critical dimensionality of asymptotically safe interactions - Eichhorn, Astrid; Schiffer, Marc (Physics letters, 2019)
We explore the question why our universe is four dimensional from an asymptotically safe vantage point. We find hints that asymptotically safe quantum fluctuations of gravity can only solve the U(1) Landau-pole problem in the Standard Model in four dimensions. This could single out the observed dimensionality of the universe as the critical dimensionality of asymptotically safe interactions.